STUDENTS’ THINKING STYLES AND ITS RELATION TO THEIR LANGUAGE LEARNING STRATEGIES - Fitria Apriani; Machdalena Vianty; Fiftinova Fiftinova (The Journal of English Literacy Education: The Teaching and Learning of English as a Foreign Language, 2017)
Abstract: The aims of this correlational study were to find out whether or not (1) there was a significant correlation between thinking styles and language learning strategies of the English Education Study Program students of FKIP Sriwijaya University, (2) there were significant correlations among each category of thinking styles to each category of languange learning strategies, and (3) there were any contributions of students’ thinking styles to their language learning strategies. The sample of this study was the English Education Study Program students of FKIP Sriwijaya University in the Academic Year 2013/2014. To collect the data, Thinking Styles Inventory (TSI) and Strategy Inventory for Language Learning (SILL) were used. The data were analyzed by using correlational and regression analyses. The result showed that there was a positive correlation between students’ thinking styles and language learning strategies. Significant correlations were also shown by each category of thinking styles and languange learning strategies. However, further calculation by using multiple regression analyses showed that the contribution of thinking styles to students’ language learning strategies was only 38.5%, suggesting that thinking styles did not give much contribution to students’ language learning strategies. It is implied that English teacher should pay attention to students’ different thinking styles and language learning strategies. Besides that, English teacher should care of other factors that can influence students’ learning.    Key words: correlation, thinking styles, language learning strategies